INNOVATIVE TECHNOLOGIES FOR THE DIFFUSE LOGISTICS OF URBAN CONSTRUCTION AND DEMOLITION WASTE - Proenca, Silton Luiz Pereira (Revista Sistemática, 2022)
The management of construction and demolition waste in urban environments represents a growing logistical and environmental challenge, particularly due to its diffuse generation pattern. Unlike centralized waste streams, construction debris is produced by numerous small and spatially dispersed sources, which complicates collection, routing, sorting, and recovery processes. This article examines the role of innovative technologies in improving the diffuse logistics of urban construction and demolition waste, with particular emphasis on drones, autonomous and semi-autonomous vehicles, and intelligent waste management systems. Drawing on recent academic literature, the discussion highlights how digital sensing, automation, artificial intelligence, and building information modeling can enhance traceability, optimize reverse logistics networks, and support circular economy objectives. At the same time, the analysis identifies key limitations related to regulatory frameworks, data interoperability, economic feasibility, and institutional coordination. The article argues that technological innovation, when integrated with governance mechanisms and market incentives, can significantly improve the efficiency and sustainability of diffuse construction waste logistics in contemporary cities.